Family business in Argentina: The discreet charm of strong ties in weak institutional contexts - Gaggero, Alejandro Javier (2023)
This article analyzes how the families of the Argentine business elite dealt with contexts of high political and economic instability, based on the cases of three families: Macri, Fortabat, and Rocca. In order to develop this objective, various sources of information used in previous research are recovered: newspaper articles from two business journals, institutional publications of firms, and semi-structured interviews with former managers.